Absorption and transport of a Mytilus edulis-derived peptide with the function of preventing osteoporosis. Issue 5 (10th February 2021) - Xu, Zhe; Fan, Fengjiao; Chen, Hui; Shi, Pujie; Zhu, Dongyang; Yang, Meilian; Wang, Zhenyu; EI-Seedi, Hesham R.; Du, Ming
Abstract : The YPRKDETGAERT peptide (PME-1) identified from the  Mytilus edulis  proteins has been shown to promote the proliferation and differentiation of osteoblasts and it has good bone-forming activity  in vitro  and PME-1 was easily absorbed in the gastrointestinal tract. Abstract : The YPRKDETGAERT peptide (PME-1) identified from the Mytilus edulis proteins has been shown to promote the proliferation and differentiation of osteoblasts and it has good bone-forming activity in vitro . Further, PME-1 has been shown to prevent osteoporosis in vivo. PME-1 can be absorbed through the gastrointestinal tract, and the passing rate in monolayer Caco-2 cells was 6.57%. PME-1 can also enter the blood circulation and the concentration of PME-1 in serum reached the maximum, 61.06 ± 26.32 ng mL −1, 20 min after feeding. The multifunctional in vivo imager was used to further determine the distribution of the 5-FITC-(Acp)-YPRKDETGAERT peptide (PME-1-FITC) 2 h after feeding the peptide, and the result confirmed the above results and showed that a part of PME-1-FITC can affect bone in vivo . Therefore, PME-1 not only was easily absorbed in the gastrointestinal tract, but also has the potential beneficial effect on preventing osteoporosis.